Bacillus vallismortis acts against ginseng root rot by modifying the composition and microecological functions of ginseng root endophytes - Hu, Yang; Yang, Liu-yang; Lei, Meng-yuan; Yang, Yi-xin; Sun, Zhuo; Wang, Wan; Han, Zhong-ming; Cheng, Lin; Lv, Ze-liang; Han, Mei; Yang, Li-min (Frontiers in Microbiology, 2025)
IntroductionThe endophytic microbiome serves a crucial function as a secondary line of defense against pathogen invasion in plants. This study aimed to clarify the mechanism of action of the ginseng plant growth-promoting rhizobacteria (PGPR) Bacillus vallismortis SZ-4 synergizing with endophytic microorganisms in the prevention and control of root rot.MethodsGinseng root samples from a susceptible group (CK) with a disease level of 0–2 and a biocontrol group (BIO) treated with strain SZ-4 were collected. We employed high-throughput sequencing to examine the microbial community structure of ginseng roots at different disease levels, explore beneficial endophytic bacteria, and evaluate the efficacy of strain SZ-4 in mitigating root rot through synergistic interactions with ginseng endophytic flora.ResultsThe application of the PGPR B. vallismortis SZ-4 biocontrol fungicide has been found to help ginseng resist Fusarium solani by modulating the richness and structure of endophytic microbial populations. The endophytic bacteria HY-43 and HY-46 isolated from ginseng roots treated with B. vallismortis SZ-4 were identified as Bacillus velezensis based on morphological, physiological, and biochemical characteristics, as well as 16S rDNA and gyrB sequencing analyses. The endophytic bacteria HY-43 and HY-46 were combined with strain SZ-4 to generate the bacterial consortia CS4-43 and CS4-46, respectively. Both CS4-43 and CS4-46 significantly enhanced the inhibitory effects of the single strain SZ-4, as well as HY-43 and HY-46, against ginseng root rot, while also promoting plant growth.DiscussionThese findings offers a theoretical foundation for studying the microecological prevention and control of ginseng diseases as well as new insights for conducting research on the efficient and precise management of plant diseases.